DISKURSUS EKONOMI ISLAM IBNU TAIMIYAH - Arifin, Mohammad; Luayyin, Reza Hilmy (JSE: Jurnal Sharia Economica, 2023)
In addition to syumuliyah (perfect), Islam is a religion that includes harakiyah (dynamic). Islam is a religion that completes all previous beliefs so that it is called perfect, so that all aspects of life are regulated according to its provisions, both those that are aqidah or muamalah. It is known that in the rules of muamalah, Islam regulates in great detail various kinds of human behavior that interact with each other in meeting the needs of life in the world. Thus it guides the market and mechanisms that cover all its principles. In the Khazanah of Islamic Economic Thought, the scholar Ibn Taimiyah studied economics in depth. Including his views on markets, prices, justice, and various other economics. This research uses descriptive qualitative research where the researcher directly examines the books of Ibn Taimiyah and other supporting literature. In this study, researchers found several Islamic economic concepts, namely fair prices/in accordance with the provisions, market mechanisms, and price regulations. Where according to Ibn Taimiyah has several different explanations according to Islamic economic thought.Keywords: Islamic Economics, Ibn Taimiyah, Market Mechanism